2019
DOI: 10.4081/pr.2019.7993
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Perineal Injury in a 13-Year-Old Female: Case Report and Review of the Literature

Abstract: Traumatic perineal injury in children is a rather underestimated condition, in terms of occurrence. The rapid stretching of the soft perineal environment, combined with the surrounding osseous tissue of the pelvis, can cause severe injuries. The key to successful management of these injuries includes timely resuscitation, thorough physical examination and quick and safe repair of damages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…An examination under anesthesia is necessary in all cases as even radiological investigations are not good enough to rule out anorectal and genital injuries. [ 2 12 ] It helps in minimizing the chances of missing an injury. It also helps in deciding the type and extent of surgical intervention; for example, the partial-thickness anorectal injury does not need a colostomy, whereas the full-thickness anorectal injury does.…”
Section: Discussionmentioning
confidence: 99%
“…An examination under anesthesia is necessary in all cases as even radiological investigations are not good enough to rule out anorectal and genital injuries. [ 2 12 ] It helps in minimizing the chances of missing an injury. It also helps in deciding the type and extent of surgical intervention; for example, the partial-thickness anorectal injury does not need a colostomy, whereas the full-thickness anorectal injury does.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma perineum pada pasien anak merupakan kondisi yang jarang terjadi. Insiden trauma perineum pada anak yaitu 4-6% (Godosis et al, 2019). Salah satu penelitian menunjukkan insiden cedera perineum pada 0,2% dari semua kejadian trauma perineum pada anak dengan usia dibawah 15 tahun (Spitzer et al, 2008).…”
Section: Epidemiologi Ruptur Perineumunclassified
“…Posterior perineal trauma is an injury to the posterior vaginal wall, perineal muscles or anal sphincter 2,3 . There is considerable variation in the number of reported incidences of perineal trauma between countries, due in part to differences in definitions and reporting practices 4,5,6 . Studies with limited use of episiotomy reported perineal trauma rates requiring suturing between 44% and 79% 7,8,9 , and a recent Cochrane Review found no evidence to support the routine use of episiotomy 10 .…”
Section: Introductionmentioning
confidence: 99%